Co-release of cytokines after drug-eluting stent implantation in acute myocardial infarction patients with PCI - Minying Wan; Kun Hu; Yi Lu; Cheng Wang; Bin Mao; Qing Yang; Zhenzhong Zheng; Hao Wu; Yihong Luo; Amit K. Maiti (Scientific Reports, 2024)
Abstract Acute Myocardial Infarction (AMI) after Percutaneous Coronary Intervention (PCI) often requires stent implantation leading to cardiovascular injury and cytokine release. Stent implantation induces cytokines production including TNFα, Hs-CRP, IL-1ß, IL2 receptor, IL6, IL8, and IL10, but their co-release is not extensively established. In 311 PCI patients with Drug-Eluting Stent (DES) implantation, we statistically evaluate the correlation of these cytokines release in various clinical conditions, stent numbers, and medications. We observed that TNFα is moderately correlated with IL-1ß (r2 = 0.59, p = 0.001) in diabetic PCI patients. Similarly, in NSTEMI (Non-ST Segment Elevation) patients, TNFα is strongly correlated with both IL-1ß (r2 = 0.97, p = 0.001) and IL8 (r2 = 0.82, p = 0.001). In CAD (Coronary Artery Disease)-diagnosed patients TNFα is highly correlated (r2 = 0.84, p = 0.0001) with IL8 release but not with IL-1ß. In patients with an increased number of stents, Hs-CRP is significantly coupled with IL8 > 5 pg/ml (t-statistic = 4.5, p < 0.0001). Inflammatory suppressor drugs are correlated as TNFα and IL8 are better suppressed by Metoprolol 23.75 (r2 = 0.58, p < 0.0001) than by Metoprolol 11.87 (r2 = 0.80, p = 0.5306). Increased TNFα and IL-1ß are better suppressed by the antiplatelet drug Brilinta (r2 = 0.30, p < 0.0001) but not with Clopidogrel (r2 = 0.87, p < 0.0001). ACI/ARB Valsartan 80 (r2 = 0.43, p = 0.0011) should be preferred over Benazepril 5.0 (r2 = 0.9291, p < 0.0001) or Olmesartan (r2 = 0.90, p = 0.0001). Thus, the co-release of IL-1ß, IL8 with TNFα, or only IL8 with TNFα could be a better predictor for the outcome of stent implantation in NSTEMI and CAD-diagnosed AMI patients respectively. Cytokine suppressive medications should be chosen carefully to inhibit further cardiovascular damage.